Uma contribuição ao estudo das tensões residuais no fresamento - Norcino, Adriana Bruno [UNESP] (2013)
Machining of moulds and dies has a promising potential of expansion and expressive economic importance. The milling process is widely used in the manufacture of mold cavities and can be a substitute to the process of EDM (EDM) and generate surfaces with better surface integrity. Residual stress may be produced in machining processes and they are the main causes of failure in structural components. This research experimentally measured the field, magnitude, depth and orientation of residual stress by using Hole Drilling Method after finishing milling of VP100 steel for moulds and dies with distinct hardness. The results where correlated with part surface microhardness, subsurface microstructure, specific cutting energy and chip-tool interface temperature. The milling tests were carried out in a CNC machining center by using 25 mm diameter endmill with two TiNAl coated carbides. The results showed residual stresses depend on cutting parameters. Tensile stress is yielded in annealed parts as the tool feed increases, whereas compressive one is generated in quenched workpieces as the cutting speed grows. Part surface hardness and cutting specific pressure presented inverse non-linear relationship with residual stress. Grains near milled surface may be deformed by mechanical action of cutting tool edge since they have preferential orientation regarding to maximum principal stresses.